298 IDENTIFICATION AND ANALYSIS OF GENES INVOLVED IN TUMOR NECROSIS FACTOR α-INDUCED INSULIN RESISTANCE. Issue 1 (1st January 2007) - Odunusi, W.; Majumdar, G.; Gerling, I.; Solomon, S.
Abstract : Metabolic syndrome is a variant of diabetes mellitus 2 (DM2), in which a major component is insulin resistance (IR). These obese individuals generate excessive amounts of the cytokine tumor necrosis factor (TNF)-α, a major cause of IR in humans. We modeled IR in H411E liver cells in tissue culture using control (C), TNF-α alone (T), insulin alone (I) and TNF-α + insulin (T + I). After extracting RNA from each of four preparations (three experiments, each preparation), the isolated RNA was analyzed on expression arrays (rat, Affymatrix). The data set query 31, 042 probesets, of which only 17, 538 were expressed and analyzed further. Of 1, 781 probesets whose expression was reduced by more than two times with I, 433 were reversed by I + T. Of these, 303 had no more than a 50% effect by T alone. Of the 1, 157 probesets increased more than two times by I, 307 were reversed by I + T, with only 189 showing an effect with T alone. We combined these positive lists, giving us a single list of 492 probesets, where expression levels were changed > two times by I and partially normalized by I + T. According to the Ingenuity Pathway Server, this list represents 154 different genes, of which 108 created 7 different networks. Conclusion: We found that when we merged these networks involving both I and T, into three final networks that those 2 genes were connected to no less than 10 other genes in each network. From these analysis, it is clear that the effected genes regulate (a) effects on signal transduction, including traditional second messengers and cytokines; (b) effects on transcription, translation, and protein synthesis and degradation; and (c) effects on energy balance, oxidation-reduction reactions, and oxidative stress.